POLITIK DINASTI DAN KRISIS LINGKUNGAN: PRAKTIK KEKUASAAN DI PROVINSI BANTEN, INDONESIA - Handoyo Handoyo (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Political power gained by political elite through "highfaluting" promises which are then converted into personal and class wealth as the cost of maintaining, affirming and abusing authority seems to be a common phenomenon in democratic country. This paper aims to reveal the practice of power in regional autonomy political system that has driven environmental crisis. Using phenomenology and discourse analysis approach, this study showed that in Banten Province, dynastic-patterned political system tends to cause natural resource crisis that trigger off some problems: 1) Excessive exploitation of nature resources with the "backing" of political elite; 2) Unintegrated inter-district development plans; 3) Environmental pollution by large industries; and 4) Inhibition of "scaling up" of environmental education projects by non governmental organizations (NGO'S). Problems that come up in Lebak regency: 1) Difficulty in reducing unauthorized gold mining activities; 2) Timber regulation that still benefits the entrepreneur; 3) Obstacles in reducing critical land; 4) Expansion process of Halimun Salak National Park is not completed yet; and 5) There is no compensation for Lebak Regency as upstream area. With the complexity of democratic political systems in the veil of capitalism and liberalism at various levels of government, this paper showed that people continue to find how difficult it is to have a good living space and justice.